Pals1 haploinsufficiency results in proteinuria and cyst formation - Weide, Thomas; Kriz, Wilhelm (Journal of the American Society of Nephrology, 2017)
The nephron is the basic physiologic subunit of the mammalian kidney and is made up of several apicobasally polarized epithelial cell types. The process of apicobasal polarization in animal cells is controlled by the evolutionarily conserved Crumbs (CRB), Partitioning-defective, and Scribble protein complexes. Here, we investigated the role of protein associated with LIN-7 1 (Pals1, also known as Mpp5), a core component of the apical membrane-determining CRB complex in the nephron. Pals1 interacting proteins, including Crb3 and Wwtr1/Taz, have been linked to renal cyst formation in mice before. Immunohistologic analysis revealed Pals1 expression in renal tubular cells and podocytes of human kidneys. Mice lacking one Pals1 allele (functionally haploid for Pals1) in nephrons developed a fully penetrant phenotype, characterized by cyst formation and severe defects in renal barrier function, which led to death within 6-8 weeks. In Drosophila nephrocytes, deficiency of the Pals1 ortholog caused alterations in slit-diaphragm-like structures. Additional studies in epithelial cell culture models revealed that Pals1 functions as a dose-dependent upstream regulator of the crosstalk between Hippo- and TGF-β-mediated signaling. Furthermore, Pals1 haploinsufficiency in mouse kidneys associated with the upregulation of Hippo pathway target genes and marker genes of TGF-β signaling, including biomarkers of renal diseases. These findings support a link between apical polarity proteins and renal diseases, especially renal cyst diseases. Further investigation of the Pals1-linked networks is required to decipher the mechanisms underlying the pathogenesis of these diseases.
Published: 06 March 2017
Gesehen am 14.06.2018